Systemic inflammatory response index as a novel biomarker for age-related macular degeneration: a cross-sectional study from NHANES (2005–2008) - Jia, Ruoshuang; Yin, Yiqing; Shan, Huimin (Frontiers in Nutrition, 2025)
BackgroundChronic low-grade systemic inflammation plays a significant role in age-related macular degeneration (AMD) pathogenesis. The systemic inflammatory response index (SIRI), a novel inflammatory marker, may predict various diseases. However, data on the relationship between SIRI and AMD are limited. This study examines the relationship between SIRI and AMD and assesses its potential as a predictive biomarker.MethodsA cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) data from 2005 to 2008 was conducted on participants aged ≥40 years with SIRI and AMD status data. Multivariable logistic regression models adjusted for confounders were used to assess the association. Sensitivity and subgroup analyses, along with restricted cubic spline (RCS) curve analysis, were performed.ResultsAmong 5,365 participants, 425 (7.9%) had AMD. The median SIRI was higher in AMD patients (1.23 vs. 1.04, p < 0.001). Higher SIRI was independently associated with increased odds (adjusted OR: 1.18, 95% CI:1.07–1.29, p = 0.001). RCS analyses revealed a dose–response relationship (p = 0.002). Subgroup analyses showed a positive association in male participants, individuals with hypertension, individuals with obesity, and non-smokers. Higher SIRI levels were independently associated with increased AMD risk (adjusted OR: 1.27, 95% CI: 1.03–1.56, p = 0.023).ConclusionElevated SIRI is independently associated with increased AMD risk in the U.S. population. SIRI may serve as a biomarker for identifying high-risk individuals, enabling early intervention. The cross-sectional design limits causal inference, and unmeasured confounders may affect the results. SIRI could potentially serve as a non-invasive biomarker for AMD risk, pending further validation through longitudinal studies.